Andrea Williams interviewed by Peter Read and Jackie Huggins in 1997 for the Seven years on - continuing life histories of Aboriginal leaders oral history project - Williams, Andrea, 1971-; Read, Peter, 1945-; Huggins, Jackie, 1956- (1997)
Williams, a filmmaker, talks about her upbringing in Perth and Katanning, W. A.; primary and secondary education and university studies; her relationship with other Indigenous people in W. A.; her strong individuality as an artist and her early determination to progress in life. She then talks about racism; tertiary studies in sculpting; her work as a film maker and her desire not to be compartmentalized as an Aborigine. Williams then discusses her parents' artistic and political backgrounds and their attitude to her work; reconciliation and her plans for the next seven years.
Preservation and cassette copies made.
Recorded on Mar. 4, 1997.
Digital master available
Uncorrected transcript (typescript, 30 leaves)
Keywords: Williams, Andrea, -- 1971- -- Interviews; Motion picture producers and directors -- Australia -- Interviews; Aboriginal Australians -- Interviews; Film producers and directors